ROAD FUND FOR SUSTAINABLE ROAD MAINTENANCE - Gatot Rusbintardjo (Himpunan Pengembangan Jalan Indonesia (HPJI), 2015)
Abstract Several roads in Indonesia are in bad conditions. It is because maintenance works is not properly conducted because of insufficiently, unsustainably, and inconsistency on allocating budget for maintenance. Insufficient or uncertain budgetary allocations to road maintenance have resulted in road deterioration that has significantly increased production and transport costs. To avoid this problem, highway professionals advocate the establishment of dedicated road funds, managed by independent road boards made up of road user representatives. So far roads maintenance in Indonesia is financed using the government budget allocation. It is difficult to give guarantee to the sustainable road maintenance if the finance for road maintenance takes from the government budget allocation. Therefore in this paper will be introduced road fund, the road maintenance funding system widely used in some countries that road conditions can be well maintained. The conclusion is that the road fund needs to be applied to maintenance the road in Indonesia. Keywords: Road, deteriorate, maintenance, road fund, budget system, sustainable Abstrak Sebagian jalan di Indonesia dalam kondisi buruk. Hal ini disebabkan karena pekerjaan perbaikan tidak dilakukan dengan baik karena kekurangan, ketidak berkelanjutan, dan ketidak konsistensi dari alokasi dana untuk pemeliharaan jalan. Kekurangan dan ketidak jelasan alokasi pendanaan untuk perbaikan jalan menyebabkan memburuknya kondisi jalan yang menyebabkan peningkatan biaya produksi dan transportasi. Untuk menghindari masalah ini, professional pengembangan jalan raya didorong untuk menciptakan dana jalan secara khusus dan dikelola oleh badan independen jalan yang terdiri dari pemangku kepentingan para pengguna jalan. Sejauh ini, pemeliharaan jalan di Indonesia dibiayai melalui alokasi dana pemerintah. Hal ini menyebabkan sulit untuk memberikan jaminan keberkelanjutan pemeliharaan jalan. Untuk ini, makalah ini mengintroduksi dana jalan untuk sistem pemeliharaan jalan yang umum digunakan di beberapa Negara yang memiliki jalan dalam kondisi terpelihara dengan baik. Kesimpulan adalah dana jalan diperlukan untuk diterapkan untuk pemeliharaan jalan di Indonesia. Kata-kata kunci: Kerusakan jalan, pemeliharaan, dana jalan, sistem pendanaan, berkelanjutan